Provision of medical waste bins (masks) in the context of preventing the spread of Covid-19 at SMK 17 Samarinda - Suwignyo; Rindha Mareta Kusumawati; Kartina Wulandari; Apriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
The East Kalimantan Covid-19 Task Force has again announced the addition of Covid-19 cases in East Kalimantan. As of December 31, 2021, the total positive cases in East Kalimantan were 158,332 cases. The status of the Covid-19 red zone is in six sub-districts, namely North Samarinda sub-district, Samarinda Ulu sub-district, Samarinda Kota sub-district, Sungai Kunjang sub-district, Sungai Pinang sub-district and Samarinda Ilir sub-district. Samarinda Seberang sub-district, Loa Janan Ilir and also in Palaran sub-district. Solutions that will be offered to these problems is mask distribution. This activity aims to increase awareness of how to properly handle mask waste. This service held in January 2022 at SMK 17 in Samarinda City. The service method used in this activity is socialization and procurement of used mask waste bins. The result of the service is that in addition to providing socialization, it also provides special trash orders for used masks so that they are not combined with other waste. The trash can provided is a trash can that can be opened without being touched, which is open via a hand sensor and can be closed automatically. The existence of the trash can is expected to increase students' attention to the importance of disposing of garbage in its place which is one of the efforts to prevent the transmission of Covid-19. The activity went smoothly with a series of activities providing material to teaching staff regarding 5M and preparation for face-to-face learning for students as well as providing New Normal equipment for schools in the form of hand washing soap, hand sanitizer, and tissue, and providing educational media in the form of banners and hand washing facilities as a means of reminder efforts in carrying out teaching and learning activities to always comply with the Health Protocol.